Former Yugoslav countries in the Balkan context and differences in their economic development - Stiperski, Zoran; Lončar, Jelena (Journal for Geography, 2008)
In this article we will talk about the perception of Balkan, how the people who lives there and people from the West see it and how it become that Balkan have so negative connotations. Also we will present how the former Yugoslav countries, as once a part of Balkan, has the different economic growth which exsisted and still exist between those countries. We will try to explain why some of them economically gone very far and others are still falling behind.